2019
DOI: 10.1002/jaba.645
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and acceptability of parent training via telehealth among families around the world

Abstract: Teaching parents to conduct functional analyses and to implement functional communication training is an efficacious approach for treating socially maintained problem behavior (Derby et al., 1997). Research has found that delivering this assessment and intervention package via telehealth technologies is efficient and acceptable to caregivers in the United States (Wacker et al., 2013b). We replicated this work with families residing in rural and urban areas of eight countries. Two behavior therapists located in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
125
0
9

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(143 citation statements)
references
References 17 publications
4
125
0
9
Order By: Relevance
“…We coded the involvement of community members in the training if they were reported to be matched in ethnicity, birthplace, current residence, or language with that of the participants. For example, Neely et al (2020) noted that "The coach was located in Japan and … spoke fluent Japanese ..." (p. 436), and Tsami et al (2019) reported that one of the trainers was "a native of Greece and had been living in the United States" (p. 1117).…”
Section: Community Outreach and Involvementmentioning
confidence: 99%
See 3 more Smart Citations
“…We coded the involvement of community members in the training if they were reported to be matched in ethnicity, birthplace, current residence, or language with that of the participants. For example, Neely et al (2020) noted that "The coach was located in Japan and … spoke fluent Japanese ..." (p. 436), and Tsami et al (2019) reported that one of the trainers was "a native of Greece and had been living in the United States" (p. 1117).…”
Section: Community Outreach and Involvementmentioning
confidence: 99%
“…Because the Georgian language did not allow for easy-to-use phrases of behavior-specific praise, the trainer used more instances of nondescriptive praise throughout the study. Tsami et al (2019) used an escape from physical touch condition during the functional analysis for one participant based on parent report of this as a common antecedent to problem behavior (in Greece, it is common practice for adults to greet children by touching their face).…”
Section: Changes In Structure and Process Of Service Deliverymentioning
confidence: 99%
See 2 more Smart Citations
“…The use of telehealth in educational and family home settings to deliver intervention to children with disabilities is also developing at a rapid rate (Tsami et al 2019). The majority of educational applications have focused on training parents and teachers in research-based interventions to address the social communication and behavioral goals of young children with autism spectrum disorder (ASD, Ferguson et al 2019).…”
Section: Introductionmentioning
confidence: 99%